A New Antibiotic for Treatment of Urinary Tract Infection -A Review Study - M Arefnezhad; E Mohammadzadeh; F Shad; F Jafarian; M Arefnezhad (Journal of Paramedical Science and Rehabilitation)
Purpose: One of the significant challenges in treating urinary tract infection (UTL) is emergence of antibiotic resistance bacteria. Gepotidacin, a new antibiotic, has been designed to combat bacterial infection, practically UTIs, and may serve as a traditional antibiotic. The present review study aims to investigate the efficacy and safely of Gepotidacin in treating UTIs, practically those caused by antibiotic resistant bacteria.Methods: A comprehensive search of PubMed and Google Scholar databases was conducted to identify relevant studies published between 2010 - 2024. The search keywords included urinary tract infection, Gepotidacin and antibiotic resistance.Results: Gepotidacin has demonstrated potent antibacterial activity against range of pathogens, including Gram-positive and Gram-negative bacteria, practically those resistant to Fluoroquinolones and other antibiotics. Minimums inhibitory concentrations (MIC) of Gepotidacin was found to be lower than that of other antibiotics, including its potential as a more effective treatment option.Conclusion: Gepotidacin is a promising antibiotic that may provide a solution to growing problems on antibiotic resistance in UTIs. Its unique mechanisms of action, which targets the DNA gyrase and topoisomerase IV enzymes, makes it an attractive alternative to traditional antibiotics.  Further studies are needed to fully explore the potential of Gepotidacin in clinical practice.